Methylation of the telomerase gene promoter region in umbilical cord blood of patients with gestational diabetes mellitus is associated with decreased telomerase expression levels and shortened telomere length - Shuhua Liu; Shuhua Liu; Shuhua Liu; Liping Xu; Liping Xu; Yan Cheng; Yan Cheng; Dehong Liu; Dehong Liu; Dehong Liu; Bin Zhang; Bin Zhang; et al. (Frontiers in Endocrinology)
ObjectiveThis study speculates that gestational diabetes mellitus (GDM) may reduce fetal telomere length (TL),which may be related to modification of methylation in the promoter region of the telomerase (TE) gene promoter region.MethodsIn this study, umbilical cord blood samples from patients with and without GDM (N = 100 each) were analyzed by prospective case-control. The TL, TE expression levels, and methylation levels of TERT and TERC gene promoter regions in two groups were measured. The significance of the methylation level of each CpG locus employed logistic regression analysis of R software, and the analysis of covariance (ANCOVA) was used to control the influence of confounding factors. Correlation analysis was performed by the Spearman.ResultsThe TL and TE expression levels of the offspring of GDM patients were decreased despite adjusting for PBMI, PWG, and TG. A total of two CpG islands were screened in the promoter region of the TERT gene and three fragments (TERT_2, TERT_3, and TERT_4) containing a total of 70 CpG sites were designed. Additionally, four CpG sites of the TERT gene in the GDM group (TERT_2_40, TERT_2_47, TERT_3_46, and TERT_3_212) showed increased methylation levels compared with the control group (all P < 0.05). In the promoter region of the TERC gene, one CpG island containing 19 CpG loci was screened and designed, and the methylation levels of the two CpG sites were significantly different in TERC_1_67 (0.65 ± 0.21 versus 0.57 ± 0.30; P = 0.040) and TERC_1_120 (0.68 ± 0.23 versus 0.59 ± 0.27; P = 0.014). The methylation levels of TERC gene fragments of GDM patients were significantly higher than those of the control group (0.69 ± 0.06 versus 0.65 ± 0.08, P = 0.001).ConclusionThis study revealed that GDM may induce decreased TE expression by increasing the methylation levels of TE genes promoter region, thereby reducing the TL.